2009
DOI: 10.1002/mop.24877
|View full text |Cite
|
Sign up to set email alerts
|

Multitunable microwave system for touchless heartbeat detection and heart rate variability extraction

Abstract: This work proposes a contactless multitunable microwave measurement scheme for heartbeat detection. Our system is based on simplicity and the ability of tuning two parameters: frequency and power. Measurements are performed at 2.4, 5.8, 10, 16, and 60 GHz. Operating at 2.4 GHz, the heartbeat signal is detected at different output power levels (from À2 down to À27 dBm). The heart rate variability is extracted for all the measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…using a concurrent dual-band system operating simultaneously at lower and higher frequencies, the advantages of increased detection sensitivity with lower noise level can be obtained and demonstrated in [1] using microstrip technology. In [10], a tunable microwave system for touchless heartbeat detection and heart rate variability extraction is proposed in which two parameters are tuned: frequency and power. Also, it is demonstrated that using the multi-tunable system, the detection sensitivity of the human vital signs can be improved.…”
Section: Performance Comparison and Discussionmentioning
confidence: 99%
“…using a concurrent dual-band system operating simultaneously at lower and higher frequencies, the advantages of increased detection sensitivity with lower noise level can be obtained and demonstrated in [1] using microstrip technology. In [10], a tunable microwave system for touchless heartbeat detection and heart rate variability extraction is proposed in which two parameters are tuned: frequency and power. Also, it is demonstrated that using the multi-tunable system, the detection sensitivity of the human vital signs can be improved.…”
Section: Performance Comparison and Discussionmentioning
confidence: 99%
“…(6) in mind, the amplitude of the received BR and HR signal is comprised of the product of J 0 (X) and J 1 (X) and the argument X is controlled by m b , m h and λ. For our current case of VSM at 60 GHz band, λ is around 4.65 mm, m b = (8 − 12)mm and m r = (0.2 − 0.5)mm for a person at rest with normal breathing [42]. Figure 9b-d shows the phase amplitude variations of R(t) signal for various combination of m b and m r with BR and HR in combined, only BR and HR, respectively.…”
Section: Applicability Of 60 Ghz Doppler Radar For Rvsmmentioning
confidence: 92%
“…An extension of the system using two antennas and operating at 60 GHz is described in [15,16]. The measurements procedure starts by sending a continuous wave signal at the desired frequency.…”
Section: Measurement Setupmentioning
confidence: 99%
“…Since the heartbeat rate is based on the detection of the signal peaks, a smoothing method is applied in order to reduce the number of surrounding peaks. This method is based on the Newton relation, which is described in [16,17].…”
Section: Measurement Setupmentioning
confidence: 99%